Antibiotic Exposure in Early Life Increases Risk of Childhood Obesity: A Systematic Review and Meta-Analysis - Shao, Xiaoqing; Ding, Xiaolian; Wang, Bin; Li, Ling; An, Xiaofei; Yao, Qiuming; Song, Ronghua; Zhang, Jin-an (Frontiers in Endocrinology, 2017)
A number of studies have previously assessed the impact of antibiotic exposure in early life on the risk of childhood obesity, but no systematic assessment is currently available. A systematic review and meta-analysis was performed to comprehensively and quantitatively elucidate the risk of childhood obesity caused by antibiotic exposure in early life. Literature search was performed in PubMed, Embase and Web of Science. Random-effect meta-analysis was used to pool the statistical estimates. Fifteen cohort studies involving 445,880 participants were finally included, and all those studies were performed in developed countries. Antibiotic exposure in early life significantly increased risk of childhood overweight (Relative risk [RR] = 1.23, 95%CI 1.13-1.35, P < 0.001) and childhood obesity (RR = 1.21, 95%CI 1.13-1.30, P < 0.001). Antibiotic exposure in early life also significantly increased the z-score of childhood body mass index (Mean difference: 0.07, 95%CI 0.05-0.09, P < 0.00001). Importantly, there was an obvious dose-response relationship between antibiotic exposure in early life and childhood adiposity, with a 7% increment in the risk of overweight (RR = 1.07, 95%CI 1.01-1.15, P=0.03) and a 6% increment in the risk of obesity (RR = 1.06, 95%CI 1.02-1.09, P<0.001) for each additional course of antibiotic exposure. In conclusion, antibiotic exposure in early life significantly increases risk of childhood obesity. Moreover, current analyses are mainly taken from developed countries, and therefore the impact of antibiotic exposure on risk of childhood obesity in vulnerable populations or developing countries still needs to be evaluated in future studies.